2018
DOI: 10.1101/276212
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measuring NDC80 binding reveals the molecular basis of tension-dependent kinetochore-microtubule attachments

Abstract: was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.The copyright holder for this preprint (which . http://dx.doi.org/10.1101/276212 doi: bioRxiv preprint first posted online Mar. 7, 2018; 2 model of the molecular basis of tension-dependent NDC80 binding to kinetochore microtubules in vivo.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Article ll OPEN ACCESS in taxol-treated cells show that the affinity of NDC80 complexes for microtubules is reduced, an event associated with increased Aurora B recruitment (Yoo et al, 2018). This may be explained by the spatial separation between Knl-pS24 and Ndc80(N) that we observe under that condition.…”
Section: Star+methodsmentioning
confidence: 58%
“…Article ll OPEN ACCESS in taxol-treated cells show that the affinity of NDC80 complexes for microtubules is reduced, an event associated with increased Aurora B recruitment (Yoo et al, 2018). This may be explained by the spatial separation between Knl-pS24 and Ndc80(N) that we observe under that condition.…”
Section: Star+methodsmentioning
confidence: 58%
“…In their study, the authors employed FRET sensors (in tubulin and the Nuf2 subunit of the NDC80 complex) to measure the fraction of microtubule-bound NDC80 complexes during metaphase chromosome oscillations in human cells. While the authors reported a statistically significant decrease of microtubulebound NDC80 complexes on poleward moving kinetochores (containing mostly depolymerizing microtubules) in comparison to those on anti-poleward moving kinetochores (containing mostly polymerizing microtubules), this difference was small (∼11% change in NDC80 complex FRET fraction), especially compared to the FRET change measured in early prometaphase with respect to late metaphase (∼50% change in FRET fraction; Yoo et al, 2018). These observations suggest that NDC80 complexes remain closely associated with the microtubule lattice on both the poleward and anti-poleward moving kinetochores of a sister pair.…”
Section: The Hec1 Tail Domain and Microtubule Dynamicsmentioning
confidence: 86%
“…All four sites were found to be phosphorylated at high levels in early prometaphase, and at much lower levels as cells progressed through metaphase and anaphase (DeLuca et al, 2011). Later studies found that expression of Hec1 mutants with increasing numbers of phospho-mimetic substitutions in the tail domain caused a corresponding decrease in kinetochoremicrotubule attachment stability in cells (Zaytsev et al, 2014;Yoo et al, 2018;Etemad et al, 2019;Kuhn and Dumont, 2019). These findings were corroborated by in vitro data revealing a direct correlation between increasing number of phospho-mimetic substitutions in the Hec1 tail domain in purified human NDC80 complexes and decreasing microtubule binding affinity (Zaytsev et al, 2015).…”
Section: Temporal Regulation Of Hec1 Tail Domain Phosphorylationmentioning
confidence: 98%
“…58 This approach was recently extended to TCSPC FLIM FRET of the interaction of Ndc80 and kinetochore microtubules in human U2OS cells stably expressing Nuf2 (a subunit of the NDC80 complex) labeled with mTq2FP, which underwent FRET with fluorescein arsenical hairpin binder (FlAsH) bound to a tetracysteine motif labeling endogenous β-tubulin. 59 We designed the methodology presented here to address the low S/N resulting from the low copy number of endogenous KPs and the strong background of cellular and culture media autofluorescence. Automated imaging with our multiwell plate FLIM microscope controlled by µManager 60 enabled the unsupervised acquisition of multiple FOVs for each yeast strain, permitting the averaging over experimental noise derived from both instrumentation and biological variability.…”
Section: Introductionmentioning
confidence: 99%